Major Concepts of the Turkey Blue Homeland Strategy - Chaban, Dariia (Mediaforum : Analytics, Forecasts, Information Management, 2023)
The article analyses the key directions of Turkey’s foreign policy under the presidency of Recep Tayyip Erdogan. It examines concepts such as “ba-lance” in relations with the Middle East and the West, which Turkey is trying to achieve through the development of its economy and international trade.  The article also focuses on the concept of “security in the East”, which reflects Turkey’s focus on security concerns from terrorist groups on its border with Syria and Iraq. Researchers on this topic also note the strategy of the “new Ottoman space”, which reflects Turkey’s intentions to increase its influence on the countries of the Balkans and the Caucasus.The article analyses the concept of “active diplomacy”, which consists in establishing diplomatic ties with new states, as well as developing and deepe-ning relations with countries that already have diplomatic ties with Turkey. In addition, the article focuses on the concept of “neighbourhood policy”, which reflects Turkey’s commitment to maintaining peace and stability in the region. The article also examines Turkey’s role in international organisations, such as NATO and the UN, and its “economic diplomacy” strategy, which reflects Turkey’s intention to attract foreign investment and develop trade relations with other countries.The Blue Homeland Strategy encompasses a number of policies and initiatives, including expanding Turkey’s naval capabilities, improving coordination between the various branches of the military, strengthening relations with allied countries, and promoting economic development in the maritime sector. The strategy emphasises the importance of diplomacy and legal initiatives to protect Turkey’s maritime rights in accordance with international law. “The Blue Homeland is seen as a comprehensive approach to addressing Turkey’s maritime security challenges and protecting its national interests. In addition, the Blue Homeland strategy also plays an important role in achie-ving Turkey’s broader foreign policy goals. The article provides an in-depth analysis of the main directions and concepts of Turkey’s foreign policy strategy, which helps to understand the complexity and importance of this country’s foreign policy activities in the modern world.